Flipped Learning Model Based on Learning Styles in Chemıstry Educatıon - Karapınar, Sema; Kadıoğlu, Nagihan; Özyalçın Oskay, Özge (Jurnal Ilmiah Peuradeun, 2023)
This study aimed to investigate the effectiveness of the flipped learning model, which was designed according to learning styles in the unit of "Acids, Bases, and Salts," compared to the traditional flipped learning model. For this purpose, the study was conducted in a pretest-posttest control group quasi-experimental design with the participation of 37 students who were 10th graders and it lasted for 7 weeks. The students in the experimental group students were taught in the flipped learning model, which was designed according to learning styles. In contrast, the ones in the control group were taught in the traditional flipped learning model. The results demonstrated that the experimental group achieved more success than the control group students taught in traditional flipped models. Besides, it was found through semi-structured interviews with voluntary students that the students generally had a positive perspective of the flipped learning model.